Comparison of tax systems of the Czech Republic and Netherlands - Podrazský, Tomáš; Morávková, Jana; Kubátová, Květa, 1952-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2016)
Bachelor thesis deals with Czech and Dutch tax system. Its aim is to analyze and describe these two different tax systems and to find out tax burden of taxpayer. The tesis is devided into four chapters. The first one deals with tax theory. The second chapter describes the tax system in Czech republic. The third chapter describes the tax system in Netherlands and the final chapter includes comparison of both tax systems. The reader of the thesis will gain complete overview of tax systems in both countries.
Vedoucí práce: Jana Morávková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses